Anatomical factors associated with gender recognizability: A study on intraoral standardized photographs. Issue 4 (16th October 2019) - Corbella, Stefano; Alberti, Alice; Muzzarelli, Martina; Zotti, Beatrice; Taschieri, Silvio; Francetti, Luca
Abstract: Aim: The aim of this research was to evaluate the possibility of identifying the sex of 1 subject through visual assessment of a frontal photograph of dentition, and to investigate if some morphological characteristics are related to sex determination. Methods: 5 expert dentists, 5 non‐expert dentists and 5 laypeople were made to watch 100 intraoral photographs for 5 seconds each and to establish their sex. The responses of the participants and the baseline characteristics of photographed dentitions were analyzed. Results: The proportion of right answers was 56.0% ± 8.2% in the group of expert dentists, 65.0% ± 6.0% in the group of non‐expert dentists and 58.6% ± 4.5% in the group of non‐expert people. The round shape of maxillary central incisors was related to the female gender ( P =  .006). The male condition was correlated with poor oral hygiene for 4 observers. Female sex perception was correlated with round morphology of upper central incisors for 3 observers. Conclusion: No difference in the ability to determine the sex was registered among groups, suggesting that sex perception is not strongly influenced by the characteristics of dentition.